Choosing the best site for a technical backfill center for urban solid waste using a multi-criteria evaluation technique based on geographic information systems. Case study of the city of M'sila - Oudina, Fateh; Benkhaled, Elhadj; Mili, Mohamed; Oudina, Fatima Zohra (Technium Social Sciences Journal, 2022)
Many wastes arise from human daily activities, and solid household waste is one of the most impactful and heavy on human shoulders, as the management of solid household waste is one of the important issues that must be taken care of in order to preserve the health and safety of humans and the environment. Therefore, this study came to identify solid household waste and the methods and methods used to manage it through collection and transportation operations until its final disposal. Geographical information systems are used in the environmental planning process in order to better plan the location of containers and identify waste collection paths, and this requires collecting data and maps for the study area to be used in the process of analyzing spatial appropriateness using geographical information systems based on planning and environmental standards to reach the best results using current-day techniques from Huge software that contributes greatly to the planning process and helps in making decisions (Geographical Information Systems "GIS", Statistical Group for Social Sciences "SPSS"). The selection of sites for technical landfill centers is of great importance at the present time, as the latter is an important and necessary issue for the sanitary disposal of waste, given the complexity of waste management systems, the selection of the appropriate urban solid waste landfill site requires consideration of alternative solutions and multiple and rather complex evaluation criteria. Where this study aims to assess the spatial suitability of the Technical Backfill Center in the city of M’sila, through a spatial analytical methodology, where the significant increase in the population of 1,276721 people in 2019 led to an increase in the quantities of produced waste that exceeded 382,038 tons / year, and thus increased rates of environmental pollution and distortion of the urban landscape. for the city. The poor location of the embankment center caused the residents to annoy, and demanded that they expedite the closure of the center despite the fact that its lifespan had not expired, which made the authorities in an embarrassing position. This is what the study provides, as the best sites were chosen for the establishment of a landfill center for the city of M'sila, so that it is difficult to change it in the future, based on a set of criteria approved by the National Waste Agency and analyzed in the GIS environment, by applying the spatial analyzer and giving weights to the criteria affecting the The site of the backfill was selected according to the relative importance of each of them by the hierarchical analysis (Ahp) process using Excel, then the Raster calculator process was performed. In our study, we tried to find an alternative site to the current site that would be more suitable than the previous one, where a set of criteria (economic, social, and environmental) were defined and using the integration of geographic information system (GIS) and the analytical hierarchy method (AHP where the GIS program plays a role). It is important in contributing to superposition analysis for landfill site selection because it has a high capacity to manage large amounts of spatial data and considers many factors from a variety of sources ,as well as its high ability to deal with the necessary social, environmental and economic constraints. this study, it was relied on using a combination of GIS and AHP programs to choose the best and most appropriate urban solid waste burial site from among the many candidate sites that meet the largest possible number of environmental and scientific criteria so that it is difficult to change it in the future, which helps officials to take the appropriate decision to achieve this goal. .The processes of choosing a landfill site includes several steps that must be performed using GIS software are: (1): The study area is divided into categories to suit the requirements, and then an appropriate weight is given to each category (2): Determining the final map of the landfill sites using the special analysis tool in GIS "Map Algebra - Single Output Map Algebra". (3): Exclusion of unsuitable areas to simplify the process of selecting candidate sites for the urban solid waste landfill center in the city of M'sila. The results showed that the best areas are likely to be suitable for the establishment of a technical landfill center for waste in the southern side (Municipality of AWLAD MADI), in the southern eastern side (Municipality of AL-MATARFA), and in the western/south side (Municipality of AWLAD MANSOUR and the lines of Dam El Geer). The study showed the location outside the city due to the lack of real estate in the city and the lack of availability of areas that meet the necessary standards for the establishment of landfill centers, and this confirms the inadequacy of the current site and the need to find an alternative site quickly. We hope that our work will provide a methodology for siting and provide basic and logistical support to decision makers in assessing waste management problems in the city and help to choose the appropriate landfill site for the city.